Digital Literasi di Pesantren Cibiru Wilayah Bandung Timur Kota Bandung Jawa Barat (Upaya Modernisasi Pengetahuan Pesantren) - Iryana, Wahyu; Sujati, Budi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2021)
Islamic educational institutions, especially Islamic boarding schools must prepare cadres of the best teachers who are not only able to read classical books, but also cadres of teachers who have broad Islamic insight with the provision of at least two international communication languages, Arabic and English. Departing from this, Journalism Literacy Literacy training in Pesentren continued to be banged on including pesantren in the Cibiru Region. This study uses a participatory observation method, researchers who involve themselves in the research object being carried out. The conclusion of the discussion that has been done is the importance of Journalism Literacy Literacy training in Pesentren to keep abreast of the times in the 4.0 revolution era. Pesantren will feel the positive impact and encourage the positive lines to queue, especially in the District of Cibiru.